Description of a new species of the genus Sarasaeschna Karube & Yeh, with a key to the species of Taiwan (Odonata: Anisoptera: Aeshnidae) - Chen, Szu-Lung; Yeh, Wen-Chi (Zootaxa, 2014)
Sarasaeschna chiangchinlii sp. nov. collected from Daxi, Taoyuan County in northern Taiwan is described and diagnosed. Judging from male penile structure, this species is considered to belong to the pryeri-group of its genus. It is easily distinguished from all known congeners in having peculiar sickle-shaped cerci in male. The habitats of S. chiangchinlii are mainly shaded brooks in lowland areas, which are exceptional for its Taiwanese relatives. Distributional maps and a key are also provided for the four species of Taiwanese Sarasaeschna.